MEASUREMENT OF SHARIA BUSINESS PERFORMANCE WITH AL-FALAH APPROACH - K, M Yusuf; Rahmah, Syahidah; Muchran, Muchriana (Institut Agama Islam Negeri (IAIN) Bone, 2023)
This study aims to conduct performance measurement analysis with Al-Falah approach. Al-Falah's approach is evaluated in accordance with Islamic law where the purpose of human life is to achieve worldly benefits and the well-being of the hereafter. The methodology used in this research is qualitative descriptive through reference studies conducted with scientific level through data collection, data reduction, data presentation, data validation and drawing conclusions. The results of the study formulate the concept of business performance through al-falah approach that balances aspects of worldly welfare and the well-being of the hereafter through eight balance indicators namely property development, worship, capacity development, spiritual development, salary eligibility, implementation of zakat, sustainability of business organization and ukhuwah in the organization.